Phytochemical profiling of underexploited Fabaceae species: Insights on the ontogenic and phylogenetic effects over isoflavone levels - Barreira, João C.M. (2018)
There is an increasing trend towards finding alternative sources of valued phytochemicals due to their diverse potentialities in food industry and pharmaceutical applications. Phenolic compounds, in particular, have been the focus of several profiling reports, but isoflavones characterization has been studied in fewer cases and in a very limited group of plant species. Despite their acknowledged bioactivity, there's actually a strict number of plants validated for their isoflavones contents. In a previous report, we have identified nine Leguminosae species (from genera Biserrula, Lotus, Ornithopus and Scorpiurus) as potential alternative sources of these phenolic compounds. However, the isoflavone profiles are highly modulated by the ontogenic stage. Therefore, the present study was conducted in the same Leguminosae species, but harvested at three sequential vegetative development stages: vegetative elongation, late bud and late flowering, with the main purpose of assessing the evolution of isoflavones content throughout the plant development. In general, the plant species from Biserrula and Lotus genera showed the highest potential as new natural sources of isoflavones, especially owing their high levels of biochanin A. Independently of the plant species, it was possible to identify the phenologic stages where each of the quantified isoflavones is maximized. These findings are useful to predict isoflavone yields according to harvesting time, validating the potential use of the studied plants in innovative food formulations.